GAGASAN KEMATIAN DAN KETUHANAN DALAM SAJAK-SAJAK ABDUL HADI WM - Wiranta Wiranta; Murtini Murtini; Asep Yudha Wirajaya (Haluan Sastra Budaya, 2019)
This research identifies deportement and concept of death from Abdul Hadi WM's poetry. Descriptive method and semiotic-structural approach were used in this research.  Descriptive method used to identifies and analyze the research object to present systematic, factual, and accurate facts and concept from its population (Dirjen Dikti, 1981: 14.) Semiotic-structural approach is used to reveal the labelling system based on elements from the poetry--that is related to each other and forms one unity of organism. By analyzing Abdul Hadi WM's poem (139 poem titles), can be concluded that (1) Abdul Hadi WM poems were built from its choose of dictions, ryhimes, arrays, and typhography so that it creates death-theme sign and (2) Abdul Hadi WM is a religious poet that can describe and write his deportment about death with subtle but strong words.